Conquering Digital Overload Leadership strategies that build engaging work cultures (Springer International Publishing, 2018)
This book examines the impact of the digital deluge on employees and organization and sets out the leadership actions needed to create a corporate culture fit for the digital age. In the digital world executives are presented with exponentially more information than their predecessors were a generation ago - and yet we're not exponentially more productive. Why? Because we're using twenty first century technology with a twentieth century mindset. Excessive working hours, email overload and invasion of private life are all symptoms of a working culture that has used technology to simply amplify old management processes rather than enable and refine newer, more productive ones. Instead of liberating us, technology has created a digital overload, accentuating the problems of presenteeism, unreasonable deadlines and management demands. Organizations need to stop using technology to turn up the volume and start using it to change the channel. Written by a unique team of experts, this edited collection covers leadership, corporate culture, technology, wellness and workplace design. It argues that digital overload is a problem of corporate culture and a failure of leadership. As such it takes leadership to fix it. Leaders who have the courage to explore alternative ways of working with technology, the enlightenment to give employees more freedom and control over their own lives, and the humility to live and demonstrate the new culture personally. Those who do this have the power transform their organizations so they can ride the digital wave rather than be swamped by it.